2013
DOI: 10.1080/08927014.2013.830108
|View full text |Cite
|
Sign up to set email alerts
|

Study of the activity of quaternary ammonium compounds in the mitigation of biofouling in heat exchangers–condensers cooled by seawater

Abstract: The effectiveness of two quaternary ammonium compounds (QACs) (non-oxidising biocides) to reduce the growth of biofilm adhering to the tubes of a heat exchanger-condenser cooled by seawater was evaluated. Their effectiveness was compared to that of a conventional oxidising biocide (sodium hypochlorite [NaOCl]) under the same testing conditions. Each biocide was applied intermittently (6 h on, 6 h off) in a first shock stage (1.5 ppm over 8 days) and a second stabilising stage (0.5 ppm over 20 days). The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…The concentration of dissolved solids was 4.7 mg cm −2 , of which 74% was inorganic matter and 26% was organic matter (Figure 4). As in previous experiments (Eguía et al 2008;López-Galindo et al 2010;Trueba et al 2013), these results demonstrated that the hydraulic-thermal conditions in the untreated heat exchanger favour the formation of biofouling on the internal surfaces of the tubes. Therefore, the effectiveness of AF treatment using EMFs could be assessed under stringent conditions.…”
Section: Evolution Of Biofouling In the Af-untreated Control Tubessupporting
confidence: 51%
See 3 more Smart Citations
“…The concentration of dissolved solids was 4.7 mg cm −2 , of which 74% was inorganic matter and 26% was organic matter (Figure 4). As in previous experiments (Eguía et al 2008;López-Galindo et al 2010;Trueba et al 2013), these results demonstrated that the hydraulic-thermal conditions in the untreated heat exchanger favour the formation of biofouling on the internal surfaces of the tubes. Therefore, the effectiveness of AF treatment using EMFs could be assessed under stringent conditions.…”
Section: Evolution Of Biofouling In the Af-untreated Control Tubessupporting
confidence: 51%
“…Measurements were taken at the end of the experiment (shutdown of the plant was necessary) using a test tube of known dimensions and weight placed at the outlet of each tube in a test tube holder system described by . The biofilm thickness was calculated in accordance with Equation 1 (Trueba et al 2013).…”
Section: Biofilm Characterisationmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanism of action of cationic surfactants (BAC, BDMDAC and CTAB) is the same as the general mechanism of QACs. The hydrophilic headgroup of QACs is adsorbed to the cell wall and reacts with the cytoplasmic mem-brane, allowing the release of intracellular constituents (Salton 1968;Ferreira et al 2011;Trueba et al 2013). The strong affinity of CTAB for the protein and lipid components of the membrane suggests that this QAC is spent before it reaches the under-layers of the biofilm (Simões et al 2006).…”
Section: Resultsmentioning
confidence: 99%